Evaluation of Latex Agglutination Test (KAtex) for Early Diagnosis of Kala-azar (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):335-9.The abstract of this article is available on the PubMed website